Blunt Traumatic Aortic Injury Management, a French TraumaBase Analytic Cohort. (March 2022) - Boutin, Louis; Caballero, Marie-Josée; Guarrigue, Delphine; Hammad, Emmanuelle; Rennuit, Isabelle; Delhaye, Nathalie; Neuschwander, Arthur; Meyer, Alain; Bitot, Valérie; Mathais, Quentin; Boutonnet, Mathieu; Julia, Pierre; et al.
Abstract : Objective: Blunt traumatic aortic injury (BTAI) in severe trauma patients is rare but potentially lethal. The aim of this work was to perform a current epidemiological analysis of the clinical and surgical management of these patients in a European country. Methods: This was a multicentre, retrospective study using prospectively collected data from the French National Trauma Registry and the National Uniform Hospital Discharge Database from 10 trauma centres in France. The primary endpoint was the prevalence of BTAI. The secondary endpoints focused chronologically on injury characteristics, management, and patient outcomes. Results: 209 patients were included with a mean age of 43 ± 19 years and 168 (80%) were men. The calculated prevalence of BTAI at hospital admission was 1% (162/15 094) (BTAI admissions/all trauma). The time to diagnosis increased with the severity of aortic injury and the clinical severity of the patients (grade 1: 94 [74, 143] minutes to grade 4: 154 [112, 202] minutes, p  = .020). This delay seemed to be associated with the intensity of the required resuscitation. Sixty seven patients (32%) received no surgical treatment. Among those treated, 130 (92%) received endovascular treatment, 14 (10%) open surgery (two were combined), and 123 (85%) were treated within the first 24 hours. Overall mortality was 20% and the attributed cause of death was haemorrhagic shock (69%). Mortality was increased according to aortic injury severity, from 6% for grade 1 to 65% for grade 4 ( p < .001). Twenty-six (18.3%) patients treated by endovascular aortic repair had complications. Conclusion: BTAI prevalence at hospital admission was low but occurred in severe high velocity trauma patients and in those with a high clinical suspicion of severe haemorrhage. The association of shock with high grade aortic injury and increasing time to diagnosis suggests a need to optimise early resuscitation to minimise the time to treatment. Endovascular treatment has been established as the reference treatment, accounting for more than 90% of interventional treatment options for BTAI.